Strategic microscheduling of movies - Niklas S. Dürr; Benjamin Engelstätter; Michael R. Ward (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We investigate how competition in product niches affects the timing of product release for experience goods using data on motion pictures in the United States. Additionally, we attempt to estimate the ultimate gain of this timing. We identify product niches that movies occupy along three different product dimensions: common actor, director, and genre. We estimate the drivers for a motion pictures weekly sales based on the variation in the level of competition in these particular niches over the movie's run in cinema. We start by showing that release dates of motion pictures are more likely to be rescheduled when there is more competition during the initially proposed release week. Next, we find that competition from movies by the same director or within the same movie genre decreases motion picture's box office revenue most. Finally, we compare a movie's actual sales to estimated sales at the originally planned release date. Rescheduled movies generate about 5.4 million more revenue as they would have at their originally proposed release date.
Keywords: D22; L21; L82; M31; 330; Non-price competition; Niche competition; Strategic timing of entry; Movie market